Influence of gamma irradiation in the antioxidant potential of chestnuts (Castanea sativa Mill.) fruits and skins - Antonio, Amilcar L. (2011)
As seasonal products chestnuts have to be postharvest treated to increase their shelf-life. The most common preservation method for chestnuts is the chemical fumigation with methyl bromide, a toxic agent that is under strictly use under Montreal Protocol due to its adverse effects on human health and environment. Food irradiation is a possible feasible alternative to substitute the traditional quarantine chemical fumigation treatment. This preliminary study evaluated the influence of gamma irradiation in the antioxidant potential of chestnut fruits and skins, through several chemical and biochemical parameters. The bioactive compounds (phenolics and flavonoids) and DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activity, reducing power and inhibition of B-carotene bleaching capacity were determined. The obtained results seem to indicate that the storage favoured chestnuts antioxidant potential. Furthermore, the application of gamma irradiation also seems to be advantageous for antioxidant activity, independently of the dose used (0.27 ± 0.04 kGy or 0.54 ± 0.04 kGy).